Disinfection of Bacteria in Water by Capacitive Deionization - Laxman, Karthik; Sathe, Priyanka; Al Abri, Mohammed; Dobretsov, Sergey; Dutta, Joydeep (Frontiers in Chemistry, 2020)
Clean water is one of the primary UN sustainable development goals for 2030 and sustainable water deionization and disinfection is the backbone of that goal. Capacitive deionization (CDI) is an upcoming technique for water deionization and has shown substantial promise for large scale commercialization. In this study, activated carbon cloth (ACC) electrode based CDI devices are used to study the removal of ionic contaminants in water and the effect of ion concentrations on the electrosorption and disinfection functions of the CDI device for mixed microbial communities in ground water and a model bacterial strain Escherichia coli. Up to 75 % of microbial cells could be removed in a single pass through the CDI unit for both synthetic and ground water, while maintaining the salt removal activity. Mortality of the microbial cells were also observed during the CDI cell regeneration and correlated with the chloride ion concentrations. The power consumption and salt removal capacity in the presence and absence of salt were mapped and shown to be as low as 0.1 kWh/m3 and 9.5 mg g-1 respectively. The results indicate that CDI could be a viable option for single step deionization and microbial disinfection of brackish water.